Women, social media, and physical appearance anxiety: The effect of sociocultural attitudes - March, Evita; Tenaglia, Louise; Wagstaff, Danielle L. (Studia Psychologica: Theoria et praxis, 2022)
In this report, we tested if viewing the body as an object (BAO; two forms: thin and curvaceous) and body as a process (BAP) on social media, and sociocultural attitudes regarding social media, directly affected women’s state physical appearance anxiety. Women (N = 249; Mage = 23.81; SD = 5.68) completed an online experiment where they were randomly assigned to view BAO-thin, BAO-curvaceous, and BAP images. Viewing BAO-curvaceous images had no effect on women’s state physical appearance anxiety. However, viewing BAO-thin and BAP images decreased women’s state physical appearance anxiety. Further, this effect was stronger for women with greater internalization and awareness of body ideals conveyed by social media (i.e., high sociocultural attitudes). We conclude that sociocultural attitudes regarding social media may buffer the adverse effects of viewing BAO-thin images.